Optimization of Biometric Authentication System Data Update in Old-Age Security Program Case Study in BPJS Ketenagakerjaan - Fitri Sya'bania, Anisa; Nisy Kenaya Ginting, Anastasia; Tjaraka, Heru; Nugroho, Yanuar (IPB University, 2025)
BPJS Ketenagakerjaan added a biometric system to the data update application feature to ensure access security. However, this has raised new discomfort from participants. Participants must come to the BPJS Ketenagakerjaan branch office if there are repeated errors in the system. The purpose of this study is to optimize the biometric authentication system for updating data. This study uses a qualitative descriptive method with a case study approach. The PIECES framework is used as a tool to analyze the biometric authentication system. Interviews, observations, and literature studies are used in data collection. Data triangulation is used to obtain appropriate conclusions and suggestions. The result show that the biometric authentication system is used to update data on the old-age security program. Face recognition is being used in biometric authentication. If the participant fails thrice in the authentication process, they must come to the BPJS Ketenagakerjaan branch office to reopen their authentication access. Optimization can be done by adding variations of biometric authentication such as fingerprints and irises, and automatically re-granting access after a 60-second cooldown without coming to the BPJS Ketenagakerjaan office.